Analysis of the Needs for Developing Multicultural Learning Media Based on Local Wisdom through Virtual Digital Storytelling to Strengthen Students’ Tolerance Attitudes in Senior High Schools in Singkawang City - Eko Wahyu Junaidi; Andang Firmansyah; Kristoforus Bagas Romualdi (Jurnal Artefak, 2025)
AbstractThis study aims to analyze the needs for developing multicultural learning media based on local wisdom through a Virtual Digital Storytelling (VDS) approach to strengthen students’ tolerance attitudes at Santo Ignasius Senior High School, Singkawang City. The research employed a descriptive qualitative design using purposive sampling. The main informants consisted of the Principal, Vice Principal for Curriculum Affairs, Vice Principal for Student Affairs, History Teacher, and a local sister (nun) figure. Data were collected through in-depth interviews, participatory observations, and documentation, and were analyzed thematically following the Miles and Huberman model (data reduction, data display, and conclusion drawing), with data validity ensured through triangulation and member checking. The findings indicate that although the school has a strong foundation of tolerance culture and supportive curricular programs (P5), there remains a pedagogical gap characterized by the dominance of conventional learning media and students’ preference for visual–interactive formats. Informants agreed on the urgency of developing VDS containing narratives of local wisdom (e.g., Cap Go Meh, Naik Dango, and interfaith traditions) to provide contextual learning experiences that foster empathy, solidarity, and cooperation among students. The study recommends developing short-duration VDS prototypes with interactive elements and mobile accessibility, conducting digital literacy training for teachers, and collaborating with local cultural figures to ensure content authenticity. The implications of this study highlight that integrating local content with narrative technology can serve as an effective strategy for instilling tolerance values in multicultural schools. Keyword: Virtual Digital Storytelling, local wisdom, multicultural education, tolerance, character education.